Hemopoiesis-stimulating effects and enhanced survival of irradiated mice after peroral or intraperitoneal administration of ultrafiltered pig leukocyte extract (UPLE, IMUNOR) - Vacek, A; Hofer, M; Hromas, J; Luksíková, E; Svoboda, J; Schneiderová, H (Immunopharmacology and immunotoxicology, 2002)
Ultrafiltered pig leukocyte extract (UPLE, IMUNOR, ImunomedicA, Ustí nad Labem, Czech Republic) administered perorally (p.o.) or intraperitoneally (i.p.) enhanced recovery of the pool of granulocyte-macrophage hemopoietic progenitor cells (GM-CFC) in the bone marrow of normal or sublethally irradiated mice and increased survival of mice exposed to a lethal radiation dose. In experiments in vitro, sera of mice treated with UPLE p.o. or i.p. induced GM-CFC colony formation in cultures of normal mouse bone marrow cells, i.e., produced colony-stimulating activity (CSA). UPLE alone did not induce GM-CFC colony growth, i.e., had no CSA. When UPLE alone or sera of mice administered UPLE p.o. or i.p. were added to bone marrow cultures containing suboptimal concentration of recombinant mouse interleukin-3 (rmIL-3), both UPLE and the sera increased the counts of GM-CFC colonies in comparison with cultures containing only rmIL-3, i.e., produced co-stimulating activity (CoSA). Based on the findings obtained in vitro, it can be hypothesized that the described CSA and CoSA of UPLE may play a role also under in vivo conditions; enhancement of the recovery of hemopoiesis suppressed by ionizing radiation may be due to co-operation of the stimulatory effects of UPLE with the action of cytokines endogenously produced in irradiated tissues.
Keywords: interleukin-3; Tissue Extracts; Leukocytes; Hematopoiesis; buněčné extrakty; radioprotektivní látky; Radiation-Protective Agents; Female; faktory stimulující kolonie; injekce intraperitoneální; hematopoetické kmenové buňky; Administration, Oral; Interleukin-3; zvířata; ultrafiltrace; myši; Injections, Intraperitoneal; Mice; Swine; hematopoéza; tkáňové extrakty; ženské pohlaví; Cell Extracts; Ultrafiltration; Hematopoietic Stem Cells; Colony-Stimulating Factors; Animals; aplikace orální; prasata; leukocyty